Phthalocyanines and Tetrapyrazinoporphyrazines with Two Cationic Donuts: High Photodynamic Activity as a Result of Rigid Spatial Arrangement of Peripheral Substituents - Ghazal, Basma; Machacek, Miloslav; Shalaby, Mona Abbas; Novakova, Veronika; Zimcik, Petr; Makhseed, Saad (Journal of medicinal chemistry, 2017)
High photodynamic activity was observed for hexadeca-cationic zinc, magnesium, and metal-free phthalocyanines (Pcs) and tetrapyrazinoporphyrazines with EC50 values as low as 5 nM (MCF-7 cells) for the best compound; this activity was several times better than that of clinically established photosensitizers verteporfin, temoporfin, S3AlOHPc, or protoporphyrin IX. This lead compound was characterized by low dark toxicity (TC50 = 369 μM), high efficiency against other cell lines (HCT 116 and HeLa), and possible activation by light above 680 nm. The excellent photodynamic activity resulted from the rigid spatial arrangement of the quaternized triazole moieties above and below the Pc core, as confirmed by X-ray crystallography. The triazole moieties thus formed two "cationic donuts" that protected the hydrophobic core against aggregation in water. The lysosomes were found to be the site of subcellular localization and were consequently the primary targets of photodynamic injury, resulting in predominantly necrotic cell death.
Keywords: Porphyrins; Pyrazoles; nádorové buněčné linie; indoly; Triazoles; Cell Line, Tumor; Humans; fotochemoterapie; triazoly; nekróza; Indoles; krystalografie rentgenová; molekulární konformace; fotosenzibilizující látky; Drug Screening Assays, Antitumor; Structure-Activity Relationship; Photochemotherapy; porfyriny; vztahy mezi strukturou a aktivitou; Necrosis; Lysosomes; lidé; Crystallography, X-Ray; pyrazoly; screeningové testy protinádorových léčiv; lyzozomy; Photosensitizing Agents; Molecular Conformation